Growing Student's Learning Interest Through the Use of Integrated E-Learning Media Daily Activities - Muhammad Ilhan Azmy; Pariz Alparuq; Rizqi Ardiansyah; Wahyudi Cahyana; Dhea Adela (Nusa Putra University, 2021)
The purpose of this research is to find out how enthusiasm and interest in learning of students during a pandemic takes place. As is the case today, all forms of community activities are limited due to the Covid-19 virus pandemic, including in the field of education which is one of the main focuses of every nation in living life. Of course, a solution is needed to be able to overcome the problem of education in the midst of this pandemic. The problem that oft en occurs in education during a pandemic is the mechanism of teaching and learning activities. The solution given in overcoming this problem is the e-learning method of learning . The e-learning method of learning is an educational system or concept that utilizes information technology in the teaching and learning process. This research was conducted using a literature study research method, which examines various reference sources, which are obtained from journals or scientific articles, both from print and online media. The results of this study are expected to increase the awareness of students in learning, even though using the e-leaning method, and so that students can adapt to the technology used